Youth-Led Legal Due Diligence: Boosting Investment Readiness in the Kebumen Geopark - Wulandari, Maria Mu'ti; Destyarini, Normalita; Wisudawati, Tri (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Kebumen Geopark has a variety of superior products such as coconut sugar, handicrafts that have high economic potential, but most business actors still face business legality obstacles such as permits, brands, and quality certifications. This low level of legal compliance lowers investor confidence and the competitiveness of market products. Purposes of The Devotion: Increasing legal capacity and business legality compliance of MSME actors in the Kebumen Geopark Area through legal due diligence education based on the role of youth. Method of The Devotion: The service activities use a participatory approach that includes legal counseling to increase understanding of the importance of business legality, as well as practical training that focuses on the preparation and management of legal documents. The service activities involved the Kebumen Investment and One-Stop Integrated Services Office and the Indonesian Chamber of Commerce and Industry Kebumen, so that the Kebumen Geopark Youth Forum received direct assistance in the process of fulfilling the business legal aspects used to increase the attractiveness of investment in the Geopark Area. Results Main Findings of the Devotion: The acquisition of the title of the Kebumen Region as a Geopark can increase the income of local residents and the region so that it can make investors interested in investing. The results showed a significant increase in participants' legal understanding by 55% from the results of post-activity post test implementation and the active involvement of more than 80% of partner members who would later be facilitators in carrying out legal due diligence. Mentoring produces an understanding related to legal due diligence in attracting investors, processes in the Geopark Region.